New physical and biological evidence of lateral transport affecting dinoflagellate cyst distribution in the benthic nepheloid layer along a land-sea transect off Figueira da Foz (Atlantic Iberian margin) - García-Moreiras, Iria; Hatherly, Melissa; Zonneveld, Karin; Dubert, Jesus; Nolasco, Rita; Santos, Ana Isabel; Oliveira, Anabela; Moita, Teresa; Oliveira, Paulo B.; Magalhães, Jorge M.; Amorim, Ana (Frontiers in Marine Science, 2023)
The production of resting cysts is a key dispersal and survival strategy of many dinoflagellate species. However, little is known about the role of suspended cysts in the benthic nepheloid layer (BNL) in the initiation and decline of planktonic populations. In September 2019, sampling of the dinoflagellate cyst community at different water depths in the water column and in the bottom sediments, and studies of spatio-temporal changes in physical properties (temperature, salinity, density and suspended sediment concentration), were carried out along a land-sea transect off Figueira da Foz (NW Portugal) in order to investigate the dinoflagellate cyst distribution and the factors (physical and biological) affecting it. A well-developed BNL was present during the survey, which covered a change from active to relaxed upwelling conditions. Using a clustering analysis, BNL and sediment cyst records were compared with the cyst rain recorded by a sediment trap at a fixed station, supporting that the main origin of cysts in the BNL was the recent production in the water column. The spatial coincidences in the distribution of cysts and vegetative cells of the yessotoxin-producer Protoceratium reticulatum also supported that full cysts in the water column were being produced in surface waters. The observation of great abundances of full cysts in the BNL and the results of excystment experiments evidenced the presence of a significant reservoir of viable cysts in the BNL that have the potential to seed new planktonic blooms. Furthermore, back-track particle modelling experiments evidenced that alongshore transport was the main physical mechanism controlling cyst dynamics in the BNL during most part of the survey period, being particularly intense in coastal stations (<100 m depth). Consequently, the sediment cyst signal is a mixture of locally and regionally produced cysts. We provide multi-disciplinary data evidencing that cysts recently formed in the photic zone can be laterally advected within the studied region through the BNL, contributing to a better understanding of the role of the BNL in cyst dynamics and trace the seed sources of the new blooms.